2015
DOI: 10.1002/mnfr.201400881
|View full text |Cite
|
Sign up to set email alerts
|

Digestive absorption of silicon, supplemented as orthosilicic acid–vanillin complex

Abstract: Although many studies have investigated the metabolism and bioavailability of Si supplemented in foods or as a food ingredient, this was the first to investigate and demonstrate the digestibility of OSA administered in a complex form with vanillin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Silicon is a microelement whose role and essentiality for the human organism remains unclear [25]. However, in view of the available research data its connection with the functioning of connective tissues seems to be unquestionable [26,27]. An association has been found between dietary silicon and bone condition in humans [28].…”
Section: Introductionmentioning
confidence: 99%
“…Silicon is a microelement whose role and essentiality for the human organism remains unclear [25]. However, in view of the available research data its connection with the functioning of connective tissues seems to be unquestionable [26,27]. An association has been found between dietary silicon and bone condition in humans [28].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent clinical trial, Marcowycz et al. reported that following ingestion of one dose of OSA–VC (12.8 mg of Si) the Si serum concentration peaks at ca. 150 μg/L, being in range with Pruska et al.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the present study was to investigate the transport mechanism of Si, supplied as an OSA‐vanillin complex (OSA–VC), across the intestinal mucosa using an in vitro model of the human intestinal barrier based on the Caco‐2 cell culture. OSA–VC is a molecule of OSA stabilized by vanillin and was recently shown to be a source of bioavailable Si, increasing the Si levels in the serum and urine of patients supplemented with OSA–VC . OSA is the main form of Si in water and in most plants .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final pH is adjusted to the value according to the proposed specifications [41]. The EFSA assessed the bioavailability of Si from OSA-VC, taking into account available studies, among others, the Marcowycz et al (2015) [49] research. This study demonstrated a significant increase of silicon concentration in plasma after oral ingestion of OSA-VC by human volunteers, with maximum concentrations obtained after 3 hours from intake.…”
Section: Silicic Acids and Their Stabilized Formsmentioning
confidence: 99%